The mediating effect of sleep disturbance on the association between hypertension and depression: a national data analysis - Kamaluddin Latief; Samuel Akyirem; Siriluk Sithichoksakulchai; Dieta Nurrika; Mokh. Sujarwadi; Faizul Hasan (BMC, 2024)
Abstract Background Sleep disturbance is a common among people with hypertension. However, the mediating role of sleep disturbance in the association between hypertension and depression remains unclear. This study aims to investigate the mediating role of sleep disturbance in the association between hypertension and depression. Materials and methods This was cross-sectional study. The data were derived from the Indonesian Family Life Survey Fifth Wave (2014-2015). We include a total of 19,138 adults' participants with age range from 18 to 65 years old who completed response on the variable of hypertension, sleep disturbance, and depression. The mediating model analysis was processed using the PROCESS macro ins SPSS from Hayes model. Results Depression was reported by 22% of total respondents. The group with hypertension showed a substantially higher prevalence of depression than non-hypertension group (P < 0.001). Hypertension had a significant overall effect on depression (β = 0.682; 95%CI 0.489 to 0.875, P < 0.001). The direct effect of hypertension on depression was significant (β = 0.418; 95%CI 0.244 to 0.592, P < 0.001) and the indirect effect that mediated by sleep disturbance was also significant (β = 0.264, 95%CI 0.174 to 0.356, P < 0.001). It is worth noting that sleep disturbance partially mediated the association between hypertension and depression. Conclusion The findings of this study indicated that sleep disturbance contributed to the etiology of depression and hypertension in adult populations. Nurses should be involved in managing sleep disturbances, such as using behavioral therapy, as it may serve as both a treatment and primary prevention measure for depression and hypertension. Graphical Abstract